Contamination by heavy metals in silver fish (Rastreneobola argentea) caught from Lakes Kyoga and Victoria, Uganda - Mbabazi, Jolocam; Wasswa, John (International Journal of Environmental Studies, 2010)
Little information exists on heavy metal contamination in silver fish (Rastreneobola argentea) caught from Lake Victoria. A large number of Ugandans consume the species. Sun-dried silver fish were collected from 10 landing sites on Lake Victoria, and from five control sites along Lake Kyoga. The finely ground fish was digested with analytical reagent grade nitric acid. Analyses were performed by atomic absorption spectrophotometry. The specimens were found to contain significantly higher levels (p ≤ 0.05) of zinc, Zn (86.1%), copper, Cu (99.1%), cadmium, Cd (99.3%) and lead, Pb (94.6%) compared with those from the control sites. The fish contamination was attributed to discharge into Lake Victoria of untreated industrial and anthropogenic effluent. Although mean Zn, Cu and Pb concentrations were still below, those of Cd were higher than the maximum permissible levels recommended by the World Health Organization (WHO). Overconsumption of the silver fish could pose Cd-related health risks.
Keywords: Lake Victoria; Lake Kyoga; Rastreneobola argentea; Contamination; Heavy metals; Uganda